Iron biofortification in quinoa: Effect of iron application methods on nutritional quality, anti-nutrient composition, and grain productivity - Lata-Tenesaca, Luis Felipe [UNESP]; de Mello Prado, Renato [UNESP]; Ajila-Celi, Gabriela Eugenia [UNESP]; da Silva, Dalila Lopes; Junior, José Sidnaldo Pinzetta [UNESP]; Mattiuz, Ben-Hur [UNESP] (Elsevier, 2023)
Biofortification of iron (Fe) in quinoa (Chenopodium quinoa) grains should have benefits for human health and food security. However, effects of this approach on productivity, as well as Fe content and grain quality remain unknown. Thus, a greenhouse experiment was conducted to determine the impacts of different methods of Fe delivery in a hydroponic system, root application (90 µmol/L), foliar spraying (9 mmol/L), combined root and foliar application, and control (no Fe). Foliar Fe application in four applications at vegetative and reproductive stages stood out from root application in promoting quinoa growth and productivity, perhaps because of greater accumulation of Fe in the plants, leading to increased photosynthetic pigments and electron transport. Foliar application of Fe also improved grain quality, as it was associated with higher Fe contents, ascorbic acid (AsA), total proteins, and manganese (Mn). In addition, there was a decrease in antinutritional compounds and phosphorus (P) in grains. Foliar Fe application can be an efficient agronomic practice to obtain Fe-biofortified quinoa grains and was associated with improved physiological responses and productivity.
Keywords: Biofortification; Chenopodium quinoa; Foliar application; Grain quality; Micronutrients